Design and Analysis of a New Type of Electro-mechanical Brake-by-wire based on Wedge Transmission - Yansong Yang; Yutao Luo; Xiaotong Xu (Jixie chuandong)
A new type of electro-mechanical brake-by-wire system based on wedge transmission is proposed for driverless vehicle，and the optimal design method of wedge transmission angle is proposed too. The parameters design and three-dimensional modeling of the braking system are carried out，and the joint simulation virtual prototype model is built in Matlab/Simulink and Adams. The simulation results show that the tracking control performance of the new braking system is good. Under the emergency braking condition，the brake coordination time is 0.19 s，the brake unloading time is 0.3 s，the steady state control error is 1.2%. Compared with the national and industrial standards，and traditional hydraulic brake system by wire，the new brake has a large lead in loading and unloading speed，good follow-up performance，and is suitable for the use of the chassis system controlled by wire.